Project-Based Learning: Encouraging Students’ to Write - Rosfita Desi Romandhoni; Cicih Nuraeni (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2022)
Writing is important in the implementation of learning. This is one of the main focuses that need to be mastered to create maximum learning. However, the weak writing ability of students can be a problem. Therefore, relevant learning methods are needed in learning activities. Looking at these problems, the researchers uses the project-based learning method to make it easier for students to practice their writing skills. The implementation of this research is to see the development of students' writing skills using the project-based learning method in the 11th class at SMA Pahlawan Toha Bandung in the 2020/2021 academic year. In obtaining the data, the researchers use a qualitative descriptive method. From the data obtained, the researchers obtains the results: (1) the project-based learning method is recommended enough to be used because it is considered effective. (2) the project- based learning method is considered to improve students' abilities, especially in creativity as well as self-confidence and group ability. (3) Students' writing ability is improved. From these results, it can be said that using the project-based learning method in the learning process can improve the writing skills of 11th class students at SMA Pahlawan Toha Bandung.